(untitled) - FAO (Rome, 1997)
The main body of the Report provides an assessment of the state of plant genetic resources for food and agriculture and current effectiveness of and capacity for their conservation, development and use. Background data, is porvideed in appendices, as well as in figures and tables following each chapter.
Keywords: plant genetics